The Structural and Optical Properties of Zinc Telluride Thin Films by Vacuum Thermal Evaporation Technique - Maki, Samir A.; Hassun, Hanan K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Different thicknesseses of polycrystalline ZnTe films have been deposited on to glass substrates by vacuum evaporation technique under vacuum 2.1x10-5 mbar. The structural characteristics studied by X-ray diffraction (XRD) showed that the films are polycrystalline and have a cubic (zinc blende ) structure. The calculated microstructure parameters revealed that the crystallite size increases with increasing film thicknesses. The optical measurements on the deposited films were performed in different thicknesseses [ 400 , 450 and 500]nm, to determine the transmission spectrum and the absorption spectra as a function of incident wavelength. The optical absorption coefficient (Î±) of the films was determined from transmittance spectra in the range of wavelength (400-1100) nm. The dependence of absorption coefficient, on the photon energy showed the occurrence of a direct transition with band gap energy from 2.24eV to 1.92eV (for ZnTe films of different thicknesseses), where with high film thicknesses there are several energy levels resulting in several overlapping energy bands in the band gap of these films. The overlapping energy bands therefore tend to reduce the energy band gap, resulting in lower band gaps for thicker films.